Diferencias en el puntaje del examen nacional de enfermería en postulantes al servicio rural y urbano marginal de salud - Asenjo Alarcón, José Ander (2021)
Objective: to determine the differences in the score of the National Nursing Exam in applicants to the Rural and Urban Marginal Health Service in Cajamarca Peru, according to the university of origin. Method: Observational, cross-sectional study, carried out in 68 applicants to the Rural and Urban Marginal Health Service 2020 - I in nursing, using the online database of the Ministry of Health. Main results: The average score obtained by the applicants of the National Autonomous University of Chota was 14.36 ± 1.09, of the National University of Cajamarca of 13.65 ± 1.40, of the Private University of Chiclayo of 12.13 ± 0.64, of the San Pedro Private University of 12.10 ± 0.84, of the Antonio Guillermo Urrelo Private University of 11.98 ± 0.70 and from the Alas Peruanas University of 11.15 ± 0.21. The overall difference in score between universities was significant (p = 0.000). General conclusion: Comparing the score obtained between pairs of universities, the National Autonomous University of Chota with the National University of Cajamarca do not present significant differences; but there are significant differences between the National Autonomous University of Chota and the Private University of Chiclayo, San Pedro Private University, Antonio Guillermo Urrelo Private University and Alas Peruanas University. Descriptors (indicating unique identifier): Nursing staff (D009740), nursing (Q000451), nursing care (D009732), nurse's role (D024802), academic performance (D000073978), health services (D006296).